IDEOLOGICAL CONSTRUCTION IN GEN Z’S SLANG ON INSTAGRAM: A CRITICAL DISCOURSE ANALYSIS - Amalia, Nabila Dhea Putri; Budiwati, Tri Rina (Universitas Islam Sumatera Utara (UISU), 2025)
This research aims to examine textual features, investigate discursive practices, and analyze social practices that reveal the ideological constructions embedded in Gen Z’s slang on Instagram, utilizing Norman Fairclough’s three-dimensional model of Critical Discourse Analysis (CDA). Data were obtained from 31 purposively selected public Instagram posts that contained frequently used slang expressions, such as